A 136-μW - Claes, W.
A single-chip 18-channel strain-gauge datalogger IC is integrated in a 0.7-μm CMOS technology. It combines a 10-μm strain-accuracy sensor interface with digital offset compensation, a wireless 132-kHz/66-kHz transceiver and a 23.4-kgates digital unit with adjustable data processing. The datalogger's maximum power consumption, including an external 2-Mb RAM, is 136μW/channel at 3.1 V.
Keywords: 3.1 V; ASIC; CMOS integrated circuits; Adjustable data processing; Autonomous datalogger; Biomedical electronics; Biomedical measurements; Bone remodeling; Clenching; Dentistry; Digital offset compensation; Digital unit; Gnashing; Inductive link; Low-power electronics; Patient monitoring; Prosthetics; Sensor interface; Strain-gauge datalogger; Unconscious nocturnal dental activities; Wireless transceiver